Mechanisms Of Opioid-Induced Hyperalgesia: Implications For Chronic Pain Management - Serani, Krisli; Aslam, Hira; Raza Naqvi, Syed Hyder; Shafqat, Shaheryar; Ririe, Avrina Kartika; Bangash, Sudhair Abbas (Journal of Neonatal Surgery, 2025)
Background: Our understanding of opioid pharmacology has expanded significantly in recent years. Both naturally occurring and synthetic opioids bind to specific receptor types, which play a key role in their effects and mechanisms of action. Objective: To provide an overview of the opioid receptor types, their classifications, associated pharmacological effects, mechanisms of dependence, and key aspects of opioid pharmacokinetics, interactions, and therapeutic uses. Methods: A comprehensive analysis of opioid receptor families, including nociceptin, mu, kappa, and delta, and their pharmacological interactions. Opioids are categorized as agonists, antagonists, partial agonists, or agonist-antagonists based on their affinity and efficacy. Results: Opioid administration commonly leads to side effects such as sedation, euphoria, analgesia, nausea, vomiting, miosis, respiratory depression, cough suppression, stiffness, constipation, facial redness and itching, urinary retention, and the potential for dependence (tolerance and abstinence). The development of tolerance and physical dependency is linked to elevated cAMP and adenyl cyclase levels. Long-term use can result in increased transcription factors, such as CREB and ΔFosB, which are associated with relapses and sustained effects. Conclusion: This study outlines the pharmacokinetics, drug interactions, and therapeutic applications of commonly used opioids, providing a comprehensive understanding of their clinical and pharmacological profiles